Katalitični antioksidanti kot nove zdravilne učinkovine - Perdih, Andrej (Farmacevtski vestnik, 2006)
Several pathological states involve the overproduction of reactive oxygen species (ROS). Manganese-containing compounds that mimic the dismutation reaction catalyzed by superoxide dismutase (SOD) disclose a novel class of potential scavengers of reactive oxygen species. These catalytic antioxidants represented by manganese-containing active agents are SOD mimetics divided into three groups by their in vitro selectivity towards the scavenging of superoxide free-radical. The class of selective catalytic antioxidants includes macrocyclics, whereas the non-selective catalytic antioxidants comprise salens and metalloporphyrins. Cardiovascular, neurodegenerative and inflammatory lung disorders are all potential targets for the future catalyticantioxidant therapy presented herein.
Keywords: antioksidanti; antioxidant; drug; katalitični antioksidanti; metaloporfirini; reaktivne kisikove zmesi; saleni; superoksid dismutaza; zdravila